Assessing feasibility, construct validity, and reliability of a new aged care-specific preference-based quality of life instrument: evidence from older Australians in residential aged care - J Khadka; C Hutchinson; R Milte; J Cleland; A Muller; N Bowes; J Ratcliffe (Health and Quality of Life Outcomes, 2022)
Abstract Background Quality of Life-Aged Care Consumers (QOL-ACC) is a new older-person-specific quality of life instrument designed for application in quality assessment and economic evaluation in aged care. The QOL-ACC was designed from its inception with older people receiving aged care services ensuring its strong content validity. Given that the QOL-ACC has already been validated in home care settings and a preference-weighted value set developed, we aimed to assess feasibility, construct validity and reliability of the QOL-ACC in residential aged care settings.  Methods Individuals living in residential aged care facilities participated in an interviewer-facilitated survey. The survey included the QOL-ACC, QCE-ACC (quality of aged care experience measure) and two other preference-based quality of life instruments (ASCOT and EQ-5D-5L). Feasibility was assessed using missing data and ceiling/floor effects. Construct validity was assessed by exploring the relationship between the QOL-ACC and other instruments (convergent validity) and the QOL-ACC’s ability to discriminate varying levels of self-rated health and quality of life. Internal consistency reliability was assessed using Cronbach’s alpha (α). Results Of the 200 residents (mean age, 85 ± 7.7 years) who completed the survey, 60% were female and 69% were born in Australia. One in three participating residents self-rated their health as fair/poor. The QOL-ACC had no missing data but had small floor effects (0.5%) and acceptable ceiling effects (7.5%). It demonstrated moderate correlation with ASCOT (r = 0.51, p < 0.001) and EQ-5D-5L (r = 0.52, p < 0.001) and a stronger correlation with the QCE-ACC (r = 0.57, p < 0.001). Residents with poor self-rated health and quality of life had significantly lower scores on the QOL-ACC. The internal consistency reliability of the QOL-ACC and its dimensions was good (α = 0.70–0.77). Conclusions The QOL-ACC demonstrated good feasibility, construct validity and internal consistency reliability to assess aged care-related quality of life. Moderate correlations of the QOL-ACC and other instruments provide evidence of its construct validity and signifies that the QOL-ACC adds non-redundant and non-interchangeable information beyond the existing instruments. A stronger correlation with the QCE-ACC than other instruments may indicate that quality of life is more intimately connected with the care experience than either health- or social-related quality of life in residential aged care settings.